A pan-cancer analysis of the role of argininosuccinate synthase 1 in human tumors - Ding, Qiang; Li, Ruiqi; Wang, Qingming; Yu, Li; Zi, Fuming (Frontiers in Oncology, 2023)
There is accumulating evidence indicating that ASS1 is closely related to tumors. No pan-cancer analysis of ASS1 was available. Here we explored the gene expression and survival analysis of ASS1 across thirty-three tumors based on the datasets of the TCGA (Cancer Genome Atlas), the GEO (Gene Expression Omnibus), and the GEPIA2 (Gene Expression Profiling Interactive Analysis, version 2). ASS1 is highly expressed in most normal tissues and is related to the progression of some tumors. We also report ASS1 genetic alteration and their association with tumor prognosis and report differences in ASS1 phosphorylation sites between tumors and control normal tissues. ASS1 expression was associated with the infiltration of cancer-associated fibroblasts (CAFs) for the TCGA tumors of BRCA (Breast invasive carcinoma), CESC (Cervical squamous cell carcinoma and endocervical adenocarcinoma), COAD (Colon adenocarcinoma), ESCA (Esophageal carcinoma), SKCM (Skin cutaneous melanoma), SKCM-Metastasis, TGCT (Testicular germ cell tumors), and endothelial cell for the tumors of BRCA, BRCA-Basal, CESC, ESCA, KIRC (Kidney renal clear cell carcinoma), LUAD (Lung adenocarcinoma), LUSC (Lung squamous cell carcinoma), SKCM, SKCM-Metastasis, SKCM-Primary, STAD (Stomach adenocarcinoma), and TGCT. The KEGG and GO analysis were used to analyze ASS1-related signaling pathways. Finally, we used Huh7 cell line to verify the function of ASS1 in vitro. After ASS1 knockdown using small interfering RNA (siRNA), the proliferation and invasion of Huh7 were enhanced, cyclin D1 was up-regulated, and anti-apoptotic protein bax was downregulated, suggesting that ASS1 is a tumor suppressor gene in hepatocellular carcinoma.Our first pan-cancer study offers a relatively comprehensive understanding of the roles of ASS1 in different tumors.